Strategi Pengembangan Usahatani Padi di Kecamatan Bungursari Kabupaten Purwakarta - Saleha, Erlia (Jurnal Ilmiah Wahana Pendidikan, 2024)
Bungursari District is one of the industrial areas in Purwakarta Regency which is targeted by agricultural extension workers to increase the rice planting index to two or three times a year. Bungursari District is close to a spring, so it is targeted to achieve this. Many obstacles must be faced to achieve IP 200 or 300, many farmers do not comply. Therefore, a rice farming development strategy is needed. The purpose of this study was to identify internal and external factors and describe the strategy for developing rice farming in Bungursari District, Purwakarta Regency. Respondents were determined deliberately, namely as many as 18 respondents consisting of farmers and stakeholders. The data analysis method used is SWOT analysis. The results showed that rice farming in Bungursari District had strengths (availability of agricultural inputs, use of superior seeds, experience in rice farming, and availability of large areas of land). Weaknesses (limited use of agricultural machinery, productivity decreases every year, farmers cannot set prices, farmer groups are less active, technology is not evenly distributed, farmer capital is limited, market access is far away, and lack of extension facilities). As well as having opportunities (availability of agricultural assistance, labor insurance for farmers, production increase program, rice farming insurance, KUR availability, and reliable extension agents). Threats from outside (pest and disease attacks, land conversion, erratic weather changes, competition with rice from other regions and cheap rice prices, high interest rates, and bank fees). The position of rice farming in Bungursari District is in quadrant III, namely facing enormous opportunities, but on the other hand facing several obstacles. The strategy is in a turn-around (W-O) position by minimizing internal problems to get better opportunities. To obtain four alternatives, namely intensification of rice farming, revitalization of facilities and infrastructure, optimizing the role of agricultural extension workers, and paying attention to the welfare conditions of farmers.